Adaptive Beam Size Design for LEO Satellite Networks with Doppler Shift Compensation - Han, Sangmin; Lee, Wonjae; Shin, Wonjae; Kim, Jae Hyun (APWCS 2022 - 2022 IEEE VTS Asia Pacific Wireless Communications Symposium, 2022)
Over the last few years, Low Earth Orbit (LEO) satellite communication systems have been gaining much attention for fulfilling seamless global coverage requirements for 5G and beyond networks. One of the critical issues in the LEO satellite links is large Doppler shift caused by extremely high mobility of the LEO satellites. Motivated by this, LEO satellite beam size problems are tackled in this paper regarding Doppler shift and the LEO satellite altitudes. We make use of a simple Doppler shift calculation method, and assume a practical Doppler shift compensation scenario to reduce the burden at the ground user terminal. Two STARLINK satellites orbital planes which are in the range of LEO and Very-Low Earth Orbit (VLEO) altitudes are used. We evaluate the bit error rate (BER) performance versus the beam size according to the satellite altitudes, carrier frequency, and subcarrier spacing of Orthogonal Frequency Division Multiplexing (OFDM). The reliable LEO satellite beam size can be decided from the simulation results. Notably, it can help design the beam size of the LEO satellite networks based on 5G standard.
Keywords: Beam size; Doppler-shift compensation; Earth orbits; Low earth orbit satellite network; Low earth orbit satellites; Orthogonal frequency-division multiplexing; Satellite altitudes; Satellite beams; Satellite network; Subcarrier spacing; Beam size; Doppler shift; Low Earth Orbit (LEO) satellite network; OFDM; Subcarrier spacing